Classification of Hadith and Its Implications for Education and Da'wah - Ahmad Syanawani; Ahmad Mohammad Tidjani (Taqriri: Journal of Al-Hadith Science Studies, 2025)
Hadith occupies a crucial position in Islamic scholarship as the second source of law after the Qur'an. The authenticity and validity of hadith have been a primary concern for scholars from the early generations of Islam to the contemporary era. This study aims to explain the classification of hadith based on their quality levels, namely authentic, hasan, da'if, and mawdhū' hadith, along with their implications for educational and da'wah practices. This study uses a qualitative method with a literature study approach to various classical and modern literature on hadith. The results show that authentic and hasan hadith can be used as evidence in establishing laws and practices, while da'if hadith can only be used in fadha'ilul a'mal under certain conditions, and mawdhū' hadith must be completely rejected. Understanding this classification of hadith is important so that educators and da'i can convey Islamic teachings authentically and scientifically, and avoid deviations due to the use of weak or fabricated hadith.